Exploratory factor analysis of constructs used for investigating research uptake for public healthcare practice and policy in a resource-limited setting, South Africa - Jerry Sigudla; Jeanette E. Maritz (BMC, 2023)
Abstract Background Low-resource settings are often less capable of responding to and implementing available quality research evidence for public healthcare practice and policy development due to various factors. In most low-resource settings, limited empirical evidence is available to help deal with localised factors that contribute to low public health research uptake, particularly from the perspective of key research stakeholders. Methods Although the study initially employed a two-phase exploratory sequential approach, this paper focuses on the results generated from a quantitative approach. Considering the determining factors that affect research uptake in the context of low-resource settings, a measuring instrument was developed and its reliability and validity were assessed using an exploratory factor analysis approach. Results A total of 212 respondents, according to their job roles and titles, were identified as researchers, front-line workers, programme managers, and directors/senior managers of higher learning institutions, indicating that the three constructs applied in the questionnaire, namely (1) individual factors, (2) organisational factors, and (3) research characteristics, demonstrated relatively high reliability with a Cronbach's alpha of greater than 0.791. Conclusion The study concludes that the instrument can potentially be used to measure factors that affect research uptake in low-resource settings.